Sleep disturbance in post COVID-19 conditions: Prevalence and quality of life - Tedjasukmana, Rimawati; Budikayanti, Astri; Islamiyah, Wardah Rahmatul; Witjaksono, Anastasia Melissa Ayu Larasati; Hakim, Manfaluthy (Frontiers in Neurology, 2023)
Post COVID-19 conditions are complaints and symptoms in patients with a history of probable or confirmed COVID-19 after three months of the onset of COVID-19 and last at least two months. About 10-20% of people may experience Post COVID-19 conditions, one of which is sleep disturbance. There is a wide range of prevalence of sleep disturbances from 6% to more than 70%. An online survey of the Post COVID-19 conditions in various countries showed that 78.58% of subjects had sleep disturbances, including insomnia, sleep-disordered breathing, central disorders of hypersomnolence, circadian rhythm sleep-wake disorders, parasomnias, and sleep-related movement disorders. Sleep disturbance can be found starting from 2 weeks until 48 weeks or more after discharge or after having a negative COVID-19 test results. Women aged less than 50 years old with severe COVID-19 infection reported a worse outcome. Several mechanisms may cause sleep disturbance in Post COVID-19 condition, namely persistent viral infection and inflammation, immunity dysregulation, and mitochondrial dysfunction. Several studies discovered sleep disturbance was a major problem that affected different domains of QoL in Post COVID-19 conditions. Significant correlation was found between several dimensions of SF-36 with moderate-to-severe insomnia in Post COVID-19 conditions. Therefore, sleep disturbance is a major problem in Post COVID-19 conditions and may affect patients’ QoL, and the existence of sleep disturbance should be a concern in Post COVID-19 conditions period. Further research is required to determine the prevalence based on agreed definition as well as methods to assess this condition and its impact on QoL.